Catch-up growth and catch-up fat in children born small for gestational age - Won Kyoung Cho; Byung-Kyu Suh (Korean Pediatric Society, 2016)
Infants born small for gestational age (SGA) are at increased risk of perinatal morbidity, persistent short stature, and metabolic alterations in later life. Recent studies have focused on the association between birth weight (BW) and later body composition. Some reports suggest that fetal nutrition, as reflected by BW, may have an inverse programing effect on abdominal adiposity later in life. This inverse association between BW and abdominal adiposity in adults may contribute to insulin resistance. Rapid weight gain during infancy in SGA children seemed to be associated with increased fat mass rather than lean mass. Early catch-up growth after SGA birth rather than SGA itself has been noted as a cardiovascular risk factor in later life. Children who are born SGA also have a predisposition to accumulation of fat mass, particularly intra-abdominal fat. It is not yet clear whether this predisposition is due to low BW itself, rapid postnatal catch-up growth, or a combination of both. In this report, we review the published literature on central fat accumulation and metabolic consequences of being SGA, as well as the currently popular research area of SGA, including growth aspects.